CONSTITUTIONAL ECONOMICS: TOWARDS A NEW QUALITY OF INTERSECTORAL REGULATION, RESEARCH, AND EDUCATION IN THE REPUBLIC OF KAZAKHSTAN (VERITAS LEGIS JOURNAL, 2026)
Kazakhstan is undergoing profound transformations of its social structure, and the state is being renewed, gradually incorporating the characteristics enshrined in paragraph 1 of Article 1 of the Constitution of the Republic of Kazakhstan, as well as the principles of fairness and accountability. Political institutions and economic relations are undergoing extensive reform. People and their well-being have been placed at the center of state policy. The efforts of the highest authorities are aimed at resolving the fundamental difficulties that arose at the beginning of the 21st century in the sphere of constitutional and legal regulation of the economy and business, and especially in law enforcement practices. Some of them are generated by the modern, unprecedented era of technological innovation, the total inclusion of digitalization and artificial intelligence in all spheres of life. Without proper legal support, they may conflict with national interests, thereby creating threats to the country's economic, financial, and technological (digital) sovereignty and even national (constitutional) security. Others are related to the imbalances that have arisen in real life. They are caused by subjective factors in our reality. Society and the state are currently working to correct them. The existing barriers in approaches between representatives of various fields of humanities knowledge, primarily economics, philosophy, political science, and sociology, are gradually being eliminated. Their methodologies must be used to maximize the implementation of constitutional values. And vice versa. At the same time, similar, more specific tasks are faced by jurisprudence (legal science): areas of law (public and private), branches (primarily constitutional law, civil, administrative, tax, environmental, labor, social security) and groups of legislation, while defining and providing adequate space for each of them with individual objects and methods of legal regulation.
Keywords: constitutional economics; scientific and educational intersectoral model; national (constitutional) security; constitutional values